Leveraging public land ownership in the urban land market for commercial property development to achieve socio-economic outcomes in South Africa - Nhiwatiwa, Shelton (Department of Construction Economics and Management, 2018)
This thesis investigated how the South African local governments in the Western Cape Province are involved in the urban land market and, specifically, land supply for commercial property development to optimise socio-economic objectives in the South African property sector. The current conditions, challenges, and opportunities were examined using a qualitative research approach, combining primary and secondary data collection methods. The data for this research was gathered from a literature review, interviews and an online survey with local government property management officials directly involved in land transactions in local governments in the Western Cape Province, South Africa. The research found that, if well-managed, public land offers opportunities to achieve government's socio-economic objectives of driving economic growth, creating employment opportunities, and advancing people economically and socially. Through their majority urban land ownership (Gelderbloem, 2012), the South African local governments in the Western Cape Province can leverage their land assets for commercial property development to achieve socioeconomic outcomes in the urban land market. Local governments can achieve this by leading, shaping and unlocking development potential through direct supply of land, land use allocation, and facilitating, expediting and incentivising development to stimulate desired catalytic property developments. Catalytic projects refer projects that stimulate development and redevelopment of surrounding properties. The land allocation and property decisions in local governments are mainly driven by socio-economic objectives where sustainable development is the top priority and financial gain, though important is not key. In order to give full effect to leading, shaping and unlocking development on public land, local governments should make conscious, calculated interventions in the land supply chain for commercial property development to ensure a healthy property market. Also, it was found that, ideally, local governments should dispose of their land with rights in place in order to realise full valuation potential on their property as well as to minimise risk to the potential developer. Lastly, it was found that land supply from local governments for commercial development is faced with a number of challenges, chief among them being: excessive legislation and compliance requirements, lack of expertise, political interference, inadequate land management systems and others. In order to optimise local government land ownership to achieve socio-economic objectives in the urban land market, it is recommended that municipalities make well thought out strategic interventions in the land market as well as invest in the establishment of land management information systems to establish comprehensive asset registers to render effective planning and programming of their land holdings. Notwithstanding the challenges faced by local governments in alienating land, local governments in South Africa can leverage their land ownership in the urban land market for commercial property development to achieve socio-economic outcomes.